Controlling sub-cycle instantaneous optical chirality in the photoionization of chiral molecules. Issue 7 (January 2020) - Rozen, S; Comby, A; Beauvarlet, S; Bloch, E; Fabre, B; Blanchet, V; Descamps, D; Petit, S; Pons, B; Dudovich, N; Mairesse, Y
Synopsis: Photoionization of chiral molecules by circularly polarized light produces characteristic photoelectron angular distributions, showing a strong forward/backward asymmetry with respect to the light propagation axis. Up to now, this process, referred to as Photoelectron Circular Dichroism, has been studied using electric fields with constant ellipticity over the optical period. In this work, we show numerically and experimentally that the chiroptical photoelectron asymmetry can be controlled by engineering the subcycle instantaneous ellipticity and chirality of the ionizing electric field.